Crisis of the Euro Zone as a Core-Periphery Problem - Peťko, Dominik; Mandel, Martin, 1962-; Houštecký, Martin; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2014)
The thesis points at roots of the euro zone crisis in its periphery. By comparing the convergence effects on PIIGS and the CEE countries, it shows that some countries should not have adopted euro and preserved national currencies instead. The proposed solution traces parallels to the USA and envisages further fiscal unionisation of the EU.
Vedoucí práce: Martin Mandel
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses